Self-Medication Application (Swamedikasi) Based on Mobile - Fetty Ferawati; Didik Setiyadi; Endang Retnoningsih (Jurnal Mantik, 2022)
The existence of the internet which is a means of providing actual information makes users obtain information through their mobile devices with mobile-based applications, including health information which is important for human life. Self-medication (Swamedication) can provide quick information about minor illnesses that can be handled independently without having to call a medical expert, patients can also take the initial steps to treat the symptoms of the disease that arise to prevent a more severe condition due to a disease that is slow to treat. Mobile devices for self-medication applications built with the Java J2ME programming language were chosen because mobile devices support Java applications. In this application, users can access information about the details of diseases classified as self-medication, including treatment, causes, and descriptions of each disease. Another feature of this application is that users can perform a search and then be connected to the web to search and display search results according to disease keywords.